Identification of volatile compounds from polyolefin used for food packaging - Su, Qi-zhi; Vera, Paula; Canellas, Elena; Nerín, Cristina (Jornada de Jóvenes Investigadores del I3A, 2018)
Identification of volatile compounds from different virgin polyolefin FCMs was carried out by GC-MS with both HS-SPME and ultrasonic extraction (UE), with the aim to obtein the most amount of volatile compounds from polyolefin. Seventy compounds were identified with 90% reliability by GC-MS with NIST 14 library, most of them are NIAS.